(untitled) (Research, Society and Development, 2021)
Entry into higher education and academic experience characterize a significant milestone that coincides with a period of psychosocial development marked by important changes, such as the period of exploration, the age of possibilities and instabilities. The study aims to outline the profile of anxiety levels in university students at a University Center and to characterize the anxiety and associated factors of these academics in the city of Teresina, Piauí. This is a study with descriptive quantitative analysis, with a sample composed of 165 subjects chosen for convenience. Inclusion criteria: students regularly enrolled at the institution; be between 18 and 40 years old; regardless of race and social class and who consented to participate in the research. Through statistical analysis, the levels of anxiety: 4 (2.4%) had the minimum classification; 9 had a mild level, with 7 (4.2%) being male and 2 (1.3%) being female; 48 had a moderate level, 26 (15.8%) were male and 22 (13.3%) were female and 104 had a level considered severe, 50 (30.3%) were male and 54 (32, 7%) female. It was found that the majority of university students had severe levels of anxiety, observing a slight majority of the serious index related to the female sex. Anxiety levels prevailed in females who do not adhere to regular physical activity. However, it is necessary to rethink the training process from admission to its conclusion, to seek assisted training, where the student is attended to in his pedagogical and emotional needs.